2010
DOI: 10.1017/s0950268810001998
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic Cryptosporidium infection in Nigerian children: risk factors with species identification

Abstract: SUMMARYA cross-sectional study was conducted to investigate risk factors for sporadic Cryptosporidium infection in a paediatric population in Nigeria. Of 692 children, 134 (19 . 4 %) were infected with Cryptosporidium oocysts. Cryptosporidium spp. were identified in 49 positive samples using PCR-restriction fragment length polymorphism and direct sequencing of the glycoprotein60 (GP60) gene. Generalized linear mixed-effects models were used to identify risk factors for all Cryptosporidium infections, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 32 publications
1
18
0
3
Order By: Relevance
“…The association between malnutrition and childhood cryptosporidiosis has earlier been reported from cross-sectional studies in Mexico 15 and Nigeria. 29 Longitudinal studies from Brazil, 44 Peru, 9 and Guinea-Bissau 45 have shown that both symptomatic and asymptomatic cryptosporidiosis have an adverse and sustained impact on child growth, the effect being more protracted in younger and malnourished children. 9 Cryptosporidiosis in malnourished children has also been associated with more severe and prolonged illness than in normally nourished children.…”
Section: Discussionmentioning
confidence: 99%
“…The association between malnutrition and childhood cryptosporidiosis has earlier been reported from cross-sectional studies in Mexico 15 and Nigeria. 29 Longitudinal studies from Brazil, 44 Peru, 9 and Guinea-Bissau 45 have shown that both symptomatic and asymptomatic cryptosporidiosis have an adverse and sustained impact on child growth, the effect being more protracted in younger and malnourished children. 9 Cryptosporidiosis in malnourished children has also been associated with more severe and prolonged illness than in normally nourished children.…”
Section: Discussionmentioning
confidence: 99%
“…More than 20 species of Cryptosporidium are recognized, but 90% of human cryptosporidiosis is attributed to Cryptosporidium parvum and Cryptosporidiun hominis [1]. Its transmission has been associated with contaminated drinking water and food, low socioeconomic status and overcrowding conditions [2]. C. parvum has a cosmopolitan distribution and its prevalence can range from 0.1% to 31.5% in developing countries [3].…”
Section: Introductionmentioning
confidence: 99%
“…Esses resultados condizem com os de outros estudos, inclusive longitudinais, que têm reportado a influência das infecções parasitárias nos indicadores antropométricos de peso e estatura das crianças [33][34][35][36][37] . O fato de, neste estudo, o crescimento ponderal e de peso para a idade no período de um ano de frequência das crianças à creche ter sido influenciado apenas pelo adoecimento por parasitose, e não por diarreia e pneumonia, pode ter explicações relacionadas com as maiores taxas de morbidade das parasitoses e sua associação tanto com diarreia crônica quanto com pneumonia 1,31,38 .…”
Section: Peso E Estatura Peso (Kg)unclassified